Intellective predictors of college performance in government trade schools in Central Visayas - Penaranda, Joel Corton 1943- (1978)
This study focused on how valid the NCEE is for screening students for trade school. The subjects used were first year college students drawn from the three trade schools in Central Visayas. It aimed to show whether NCEE scores predict college performance in trade schools, and whether NCEE subtests predict college achievement as well. Correlational analysis was used to interpret the performance during the NCEE and on their final grade on certain subjects. According to this study, NCEE scores do not predict college performance in trade school; that the first semester performance of a student better predicts the second semester performance; that high school grades better predict general performance in college; and, when NCEE and high school grades are combined the efficacy for achievement was not increased.
Appendices: leaves 89-124
Mimeographed.
Thesis (M.Ed.)--University of the Philippines, quezon City
Vita
Keywords: Academic achievement; College students -- Philippines -- Central Visayas